Historical Sources of Folklore - Brzhozovs’ka, Svitlana (Pedagogical Discourse, 2012)
The article examines historical turns of folklore and folk songs. Education of a personality by means of folklore promotes formation of internal behavior regulators. Characteristic of the history of the historical sources of folklore is provided. The key items of folklore history are highlighted.